A systematic review of longitudinal associations between reaction time intraindividual variability and age-related cognitive decline or impairment, dementia, and mortality - Haynes, B; Bauermeister, S; Bunce, D (Cambridge University Press, 2017)
Objectives: Intraindividual variability (IIV) in reaction time refers to the trial-to-trial fluctuations in responding across a given cognitive task. Cross-sectional research suggests that IIV increases with normal and neuropathological ageing and it may serve as a marker of neurobiological integrity. This raises the possibility that IIV may also predict future cognitive decline and, indeed, neuropathology. Therefore, we conducted a systematic review to address these issues. Methods: A search of electronic databases Embase, Medline, PsycINFO, and Web of Science was completed on May 17, 2016 that identified longitudinal investigations of IIV in middle-aged or older adults. Results: A total of 688 studies were initially identified of which 22 met the inclusion criteria. Nine included longitudinal IIV measures and 17 predicted subsequent outcome (cognitive decline or impairment, dementia, mortality) from baseline IIV. The results suggested IIV increased over time, particularly in participants aged over 75 years. Greater baseline IIV was consistently associated with increased risk of adverse outcomes including cognitive decline or impairment, and mortality. Conclusions: Increased IIV over time is associated with normal ageing. However, further increases in IIV over and above those found in normal ageing may be a risk factor for future cognitive impairment or mortality. Measures of IIV may, therefore, have considerable potential as a supplement to existing clinical assessment to aid identification of individuals at risk of adverse outcomes such as dementia or death.